Adición de la Caesalpinia spinosa (Molina) Kuntze “tara” en dietas de Cairina moschata y su efecto sobre sus variables productivas - Centeno Guzmán, Lizeth Angélica María (2019)
The objective of the investigation was to evaluate the Addition of Caesalpinia spinosa (Molina) Kuntze "tara" in Cairina moschata diets and their effect on their productive variables. 180 Muscovy ducks, one week old, were selected. They were distributed under a randomized complete block design, until the ducks were 10 weeks old, and then a complete randomized design was used for the 11th and 12th week of age in the male ducks, with 3 treatments, T0: control (without tare flour), T1: tare flour in doses of 1 kg / t of food and T2: 2 kg / t of food. For weight gain, feed consumption and carcass performance, significant statistical differences between treatments (p <0.01) are determined, with T1 and T2 being higher than T0. For the nutritional conversion, percentage of morbidity and mortality, no statistical differences were determined between treatments (p> 0.05), but numerically if there is a difference, T2 being better than T1 and T0. It was determined that the sex of the duck had a significant effect (p <0.05), indicating that male ducks had better results than females, for variables such as weight gain, food consumption and feed conversion. For weeks 11 and 12 no statistical differences between treatments (p> 0.05) were determined for any productive variable. The best economic efficiency is presented by T2, followed by T1 and finally T0. It is concluded that adding tare flour in duck diets improves productive variables and economic efficiency